2013
DOI: 10.4172/2153-0645.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Functional Polymorphisms in Three Pharmacokinetic Genes of Clinical Interest within the Admixed Puerto Rican Population

Abstract: Objective This cross-sectional study was aimed at determining the allele frequencies for the CYP2C19*2, CYP2C19*3, CYP2D6*10 and PON1 (rs662) polymorphisms in the Puerto Rican population. The CYP2C19, CYP2D6 and PON1 genes are known to be associated with functional changes in drug metabolism and activation. Individuals carrying the aforementioned polymorphisms are at a higher risk of suffering from drug-induced adverse events and/ or unresponsiveness from a variety of drugs that includes antidepressants, atypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…CYP2C19*2 (681G > A) and CYP2C19*3 (636G > A) are the most prevalent alleles and have been widely studied in different populations. Previous reports have revealed that CYP2C19*2 is much more frequent in East Asians compared with populations in other distributions (Orengo-Mercado et al, 2013). Similarly, CYP2C19*3 occurs in Chinese Han subjects at a frequency of approximately 5.41%, while only 0.6% and 0.2% of African-Americans and Caucasians carry this defective allele (Bozina et al, 2003;Hu et al, 2012;Masimirembwa et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
“…CYP2C19*2 (681G > A) and CYP2C19*3 (636G > A) are the most prevalent alleles and have been widely studied in different populations. Previous reports have revealed that CYP2C19*2 is much more frequent in East Asians compared with populations in other distributions (Orengo-Mercado et al, 2013). Similarly, CYP2C19*3 occurs in Chinese Han subjects at a frequency of approximately 5.41%, while only 0.6% and 0.2% of African-Americans and Caucasians carry this defective allele (Bozina et al, 2003;Hu et al, 2012;Masimirembwa et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
“…In previous studies, the CYP2C19 * 2 variant was present in 0.09–0.148 of the Puerto Rican population, while the *3 allele was found with a frequency of 0.035 in the studied group [6668] (Table 2). Another study that used a PG array to interrogate 222 genes of cardiometabolic relevance in 71 genomic DNA specimens from Puerto Ricans found CYP2C19 * 3 allele frequencies of 0.05 among individuals of higher Amerindian heritage, 0.037 among subjects of greater European contribution, and 0.021 among those showing high African ancestry compared to the expected HapMap values of 0.056, 0.017, and 0.003 for each ancestral population, respectively [68].…”
Section: Cyp2c19mentioning
confidence: 78%
“…CYP2D6 *3 and *6 and duplications (*1XN, *2XN, *4XN, *10XN, *17XN, *35XN, and *41XN) were not found [79]. The CYP2D6 *10 variant was found with a frequency of 0.09 in 100 Puerto Rican newborn dried blood samples by Orengo-Mercado et al [66], this frequency being higher than the one found in the patient cohort of 45 patients studied by González-Tejera (0.044) [79]. MAFs from 55 Puerto Ricans reported by the 1000 Genomes Project for CYP2D6 *4 and CYP2D6 *41, among others, are shown in Table 3.…”
Section: Cyp2d6mentioning
confidence: 99%
“…Furthermore, reports showed that individual carriers of the CYP2C19 * 2 allele are at 3 times greater risk of stent thrombosis than non-carriers among the Thai population [23]. It is caused by a single-nucleotide polymorphism (G > A) in exon 5 of the CYP2C19 gene, leading to an aberrant splice site [24,25]. The second defect, CYP2C19 * 3 allele, which accounts for approximately 5% in the Chinese and 25% of Japanese PM alleles, also involves a single nucleotide exchange of G > A at position 636, which generates a premature stop codon and creates a truncated protein, which is responsible for the PM phenotype.…”
Section: Discussionmentioning
confidence: 99%